El género calopappus (compositae, mutisieae) (1986)
The suffrutex genus Calopappus of Compositae (Mutisieae, Nassauviinae) from central Chile that contained hitherto two species is considered in this study as a monotypic genus. The single species C. acerosus Meyen is described and illustrated (external morphology, palinology, leaf anatomy and geographical distribution). This taxon shows closer affinities with Nassauvia and T riptilion. However, Calopappus is differentiated of them principally by its pollen morphology  and capitula solitary respectively.